"Beyond the crude oil and gas reserves" : a comprehensive guide to investment opportunities in the petroleum and petrochemical downstream industries in Nigeria - Sote, Kayode (Lagos, Nigeria : Lubeservices Associates, 1993)
Promotes awareness for the varied investment potentials abound in the oil and gas industry in Nigeria, even beyond the estimated depletion date of proven petroleum reserves. it also addresses other issues relevant to the development of the petroleum industry in Nigeria and the world at large.
oif 23/02/15
Loan
Keywords: Petroleum industry and trade -- Nigeria; Petroleum products -- Nigeria